STRATEGI PEMBERDAYAAN MASYARAKAT DESA KEBUN MENUJU DESA MANDIRI MELALUI OPTIMALISASI KOMODITAS KACANG TANAH - Kurniyanto, Ifan Rizky; Destiarni, Resti Prastika; Arifiyanti, Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Kebun Village is one of the villages located in Kamal District, Bangkalan Regency The characteristics of the land in this village are dry land, so it is necessary to match the commodities to be developed with the characteristics of the existing land. The purpose of this study is to identify the condition of the community in Kebun village, then develop an empowerment strategy through optimization of superior commodities. The methods used in this study were RRA (Rapid Rural Appraisal) and PRA (Participatory Rural Apraisal) combined with interview techniques to informants, namely village officials and farmer groups Karya Mulya in Desa Kebun. The results of this study were known that peanut commodities could be a leading commodity in Kebun Village. The community in Kebun village needed to develop to optimize the potential in Kebun Village through collaboration with BUMDes